2012
DOI: 10.1074/jbc.m111.324673
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of the Inhibitory Effects of Bovine Lactoferrin on Lipopolysaccharide-mediated Osteoclastogenesis

Abstract: Background:We previously reported that bovine lactoferrin (bLF) reduces LPS-induced bone resorption. However, it was not clear how bLF inhibits LPS-mediated osteoclastogenesis through osteoblasts. Results: bLF impaired LPS-mediated NFB activation by interfering with TNF receptor-associated factor 6 (TRAF6) polyubiquitination. Conclusion: bLF is a potent anti-inflammatory agent. Significance: bLF may hold promise as a therapeutic agent for inflammatory diseases associated with bone destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 39 publications
1
59
0
3
Order By: Relevance
“…The present study's immunohistochemical findings also revealed that orally administered LbLF markedly downregulated LPS‐induced TNF‐α immunolocalization in the PDL, mainly in the alveolar crest. In a previous study, we have shown that bLF inhibited TRAF6‐dependent activation of the NF‐κB signaling pathway in osteoblasts 16 . Notably, it was demonstrated that internalized bLF binds to TRAF6, resulting in the inhibition of TRAF6‐mediating signaling pathway.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The present study's immunohistochemical findings also revealed that orally administered LbLF markedly downregulated LPS‐induced TNF‐α immunolocalization in the PDL, mainly in the alveolar crest. In a previous study, we have shown that bLF inhibited TRAF6‐dependent activation of the NF‐κB signaling pathway in osteoblasts 16 . Notably, it was demonstrated that internalized bLF binds to TRAF6, resulting in the inhibition of TRAF6‐mediating signaling pathway.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, we reported that orally administered liposomal bLF (LbLF) inhibits LPS‐induced periodontal tissue breakdown in rats by suppressing TNF‐α production from cells of the periodontal tissue 15 . Notably, we demonstrated that bLF impairs LPS‐mediated TNF‐α and receptor activator of nuclear factor‐κB (NF‐κB) ligand (RANKL) production by inhibiting NF‐κB activation through interaction with TNF receptor‐associated factor 6 (TRAF6) 16 . In addition, a human trial of LbLF supplementation showed the efficacy of this treatment for periodontal disease 17 .…”
mentioning
confidence: 99%
“…Focusing on cell behavior in response to LF and HA, the three conjugates with different amounts of protein attached onto HA nanocrystals, HA–LF (a), HA–LF (b), and HA–LF (c), were initially evaluated. Moreover, physiological concentration of LF (10 µg mL −1 ) that has recently showed in vivo to have a role in bone growth, healing and a potential therapeutic role as an anabolic factor in osteoporosis was also tested . The results showed no differences in cell proliferation among all the groups for the first 4 days of culture.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, lactoferrin inhibits lipopolysaccharide-induced DNA-binding activity of NF-κB, as well as IκBα and IKKβ phosphorylation [22]. We hypothesized that the inhibition of colitis-associated colorectal dysplasia by lactoferrin in mice may be related to its anti-inflammatory function.…”
Section: Resultsmentioning
confidence: 99%